DIGITAL PANTUN AS A LITERARY CRITICISM ECO-CRITICS: AN IMAGINATIONAL SPACE FOR IMPROVING EXPRESSION AND SOCIAL INTERACTION FOR PEOPLE WITH MENTAL DISABILITIES - Irfai Fathurohman; Nur Mahardika; Himmatul Ulya; Wawan Shokib Rondli; Riyan Dwi Cahyaningsih (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The lack of creative expression space that is able to integrate literary aesthetic values with psychosocial functions, especially in building emotional balance and social interaction for people with mental disabilities, is an urgent issue in this study. The purpose of this study is to examine and develop the utilisation of digital pantun as a form of ecocriticism and literature criticism, as well as an imagination therapy medium for people with mental disabilities. The relationship between humans and nature, as expressed through ecological symbols and the imagination in the pantun, makes ecocriticism relevant to this research. The research method uses an interpretative qualitative approach with eco-critical analysis of digital pantun texts, as well as participatory observation and in-depth interviews to see the impact of the application of digital pantun in imagination therapy activities at the Muria Jaya Social Service Centre (RPSDM) Muria Jaya Kudus Regency. Research results show that digital pantuns infused with ecological imagination can be a fun means of expression, facilitating social communication among beneficiaries and building simple environmental awareness through poetic language. The integration of eco-criticism and imagination therapy forms an innovative model that not only strengthens the academic study of literature but also makes a real contribution to improving the quality of life for people with mental disabilities. This study confirms that literature, especially pantun, has social and therapeutic transformational power when contextualised in digital space and inclusive practice.